PENGEMBANGAN MATERI PENYESUAIAN DIRI SISWA KELAS XI IPS3 SMA NEGERI 2 TAMBANG KABUPATEN KAMPAR TAHUN AJARAN 2013/2014 - Nur Hasanah; Sardi Yusuf; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abtract: The lack of a positive self adjusment of students and limited material about self adjusment, encourage the researcher to conduct a development research that a compilation self adjusment of material class XI IPS3 SMAN 2 Tambang students. The aimed of research: 1). Compose material adjusment of self that is suitable for students of class XI IPS 3 SMAN 2 Tambang in terms of clarity, aspects, systematics, image support, update, and completeness of the materials. 2) To Know the quality of materials self adjusment that produced. using of research and development method. as validators are guidance lecturer I, guidance lecturer II, one of BK FKIP UR lecturer, tutor teacher, 6 friends of the associate PL-BKS, and 30 students of class XI IPS3 SMAN 2 Tambang. The material self adjusment consists of 4 sub chapter : 1).the meaning of self adjusment. 2). Aspects of self adjusment. 3). Forms of self adjusment. 4). Factors that influenced self adjusment. Quality of self adjusment materials that produced based of clarity aspect is very good with X = 3,65. Systematic aspect is good with X = 3,27. Image support aspect is good with X = 2,87. Update of material aspect is good with X =3,32. Compliteness of materials aspect is good with X = 3,32. And from all of aspect is concluded good quality, with X = 3,27.Key Words: Material of self adjusmentWISUDA OKTOBER